Failure analysis of auxiliary support bearing/shaft tribopair in seawater hydraulic axial piston pump. (April 2023) - Nie, Songlin; He, Hao; Ji, Hui; Nie, Shuang; Yan, Xiaopeng; Yin, Fanglong
Highlights: Improper radius fitting clearance in auxiliary support bearing tribopair leads to damage of SHAPP. A parameterized numerical model based on nonlinear dynamic theory to analyze dynamic characteristics. Optimal radius fitting clearance for auxiliary support bearing is determined. Nonlinear shaft centerline orbit of auxiliary support bearing in SHAPP operation is analyzed. Abstract: The auxiliary support structure is used to prevent the cylinder block from tilting in seawater hydraulic axial piston pump (SHAPP). The failure modes of auxiliary support bearing and shaft under different material combinations were compared. Experimental results show that improper design of radius fitting clearance in auxiliary support bearing/shaft tribopair will seriously affect the normal operation of SHAPP and even lead to its damage. Based on the inertia force, nonlinear water film force and dynamic load balance of the rotating cylinder block, the mathematical model of the nonlinear shaft centerline orbit of the auxiliary support bearing was established. The nonlinear shaft centerline orbit of auxiliary support bearing in the cylinder block bore during SHAPP operation is analyzed accurately. Simultaneously, the water film pressure field under different radius fitting clearance is simulated and the range of the optimal value is determined. The running-in experiment of SHAPP is carried out under the optimum clearance of the auxiliary support bearing/shaft tribopair. The results show that the SHAPP can run normally and the performance is obviously improved without the wear on the friction pair surfaces. Therefore, the proposed method has provided the guidance reference for the design of auxiliary support bearing in SHAPP.